Development of haptic feedback joystick on powered wheelchair for obstacle avoidance - Ang, Chin Xian (Nanyang Technological University, 2021)
Haptic joystick is an interface incorporating force feedback to enhance the task performance and improve reaction time of wheelchair drivers. It is able to help the wheelchair drivers with visual impairment to compensate for the lack of visual information and raise their situational awareness by introducing haptic feedback. Most of the joystick design are inefficient in terms of energy transmission and focus on active force feedback. This project presents a development of a 2 degree of freedom (DOF) haptic joystick with direct-drive mechanism for efficient energy transmission. The force feedback is powered by 2 high torque direct drive brushless DC motor (BLDC) connected in gimbal structure for decoupled mechanism and stiffen control. The project also focuses on passive force feedback mechanism with the BLDC being programmed as spring and damper system using proportional-derivative (PD) controller. The joystick stiffness of the virtual spring would increase based on level of dangerousness computed by obstacle avoidance algorithms. As user move closer to obstacle, a larger stiffness would be produced. Thus, preventing user from moving into that particular direction. Lastly, three obstacle avoidance algorithms, namely Dynamic Window Approach(DWA), Potential Field Algorithm(PFA) and Obstacle Dependent Gaussian Potential Field Algorithm(ODGPFA), are integrated into the haptic feedback algorithms. An experiment was carried out where participants are required to drive a series of obstacle course to evaluate both the effectiveness of the haptic feedback system and the compatibility of the three different obstacle avoidance algorithms. Results shows that haptic joystick helps to reduce number of collisions. However, it increases the time taken to completion due to more difficult to accelerate caused by stiffen haptic joystick. According to user reviews, it shows that ODG-PFA has the best compatibility with the feedback mechanism due to its advancement in identifying obstacle and steady force increment.